Hippocampal Representations of Event Structure and Temporal Context during Episodic Temporal Order Memory. (28th August 2021) - Liu, Chuqi; Ye, Zhifang; Chen, Chuansheng; Axmacher, Nikolai; Xue, Gui
Abstract: The hippocampus plays an important role in representing spatial locations and sequences and in transforming representations. How these representational structures and operations support memory for the temporal order of random items is still poorly understood. We addressed this question by leveraging the method of loci, a powerful mnemonic strategy for temporal order memory that particularly recruits hippocampus-dependent computations of spatial locations and associations. Applying representational similarity analysis to functional magnetic resonance imaging activation patterns revealed that hippocampal subfields contained representations of multiple features of sequence structure, including spatial locations, location distance, and sequence boundaries, as well as episodic-like temporal context. Critically, the hippocampal CA1 exhibited spatial transformation of representational patterns, showing lower pattern similarity for items in same locations than closely matched different locations during retrieval, whereas the CA23DG exhibited sequential transformation of representational patterns, showing lower pattern similarity for items in near locations than in far locations during encoding. These transformations enabled the encoding of multiple items in the same location and disambiguation of adjacent items. Our results suggest that the hippocampus can flexibly reconfigure multiplexed event structure representations to support accurate temporal order memory.